Income shocks, household job search and labor supply - Gonçalves, Solange Ledi (2017)
Analyses about aggregate employment, unemployment, and inactivity rates frequently disregard labor market trends of specific household members, which may explain some puzzles in the relationship between economic activity and labor market participation. The relevance of family approaches of labor supply transcends the aggregate macroeconomic trends and addresses important micro-level analysis concerning the behavior and intrahousehold decisions of members and policy-relevant results. Despite the consensus about the joint labor supply decisions of household members, studies are typically at the individual level and disregard sons and daughters as decision-makers in a family. Therefore, in this thesis, we investigate these questions for Brazil, in two studies. In the first study, we analyze the labor supply decisions of sons daughters aged 14 to 24 years living with their parents, in a reduced form exercise. We collaborate to the empirical literature about intrahousehold impacts of policies, testing whether the minimum wage, which affects the income of parents, impacts the final labor supply decisions of sons and daughters. We also verify if the policy has distinct effects depending on whether the eligible person is the father or the mother, aiming to test the income-pooling hypothesis. Our identification strategy is based on an intention-to-treat approach, and in a differences-in-differences estimator. Another innovation is the use of the PNADC (IBGE) for 2012-2016. We find that the direction and magnitude of the minimum wage effects affecting fathers and mothers, on the labor supply of sons and daughters, depend on who is and how many eligible members there exist in the household: it is negative, whether the eligible person is the mother or the father, and it is positive, whether both are eligible. Therefore, our results strengthen the argument in favor of household approaches, since the income pooling hypothesis does not seem to be valid in this context. In the second study, we investigate how the decisions about labor supply could determine the aggregate results of unemployment and inactivity of the secondary household earners. We develop and estimate a structural household job search model with on-the-job search. We extend Dey and Flinn (2008) to allow for unemployment and inactivity of mothers and sons and daughters who are subject to shocks to their employment and income shocks to fathers. These shocks may determine different search behavior and job acceptance, depending on the other household member\'s labor market situation. The model is estimated using the PME (IBGE) for 2004-2014. We perform counterfactual simulations, and we verify that the decreasing unemployment rate of sons/daughters would not have changed between 2004 and 2014 if the labor market opportunities and conditions of this member remain the same. The unemployment rate of mothers does not alter a lot in this period. The increasing trend in the inactivity of sons/daughters is mostly determined by a decreasing encouragement rate and the increasing dropout rate observed among these members in this period. These exogenous factors that determine the move to or the permanence in the inactivity could be related to the lower cost of education. We conclude that the use of individual job search models to understand aggregate unemployment and inactivity can be misleading, since the household search behavior matters in the labor supply decisions of secondary household earners.